Price setting and the steady-state effects of inflation - Miguel Casares (European Central Bank (ECB), 2002)
This paper examines how price setting plays a key role in explaining the steady-state effects of inflation in a monopolistic competition economy. Three pricing variants (optimal prices, indexed prices, and unchanged prices) are introduced through a generalization of the Calvo-type setting that allows the possibility of price indexation, i.e., prices may be adjusted by the rate of inflation. We found that in an economy with less indexed prices the steady-state negative impact of inflation on output is higher. In the extreme case without no price indexation at all (purely Calvo-type economy), unrealistically heavy falls in capital and output were reported when steady-state inflation increases. Regarding welfare analysis, our results support a long-run monetary policy aimed at price stability with a close-to-zero inflation target. This finding is robust to any price setting scenario.
Keywords: E13; E31; E50; 330; price setting; superneutrality; welfare cost of inflation